Evaluation of the corrosion protection of coatings derived from soybean-based epoxy resin - Yeo, Darwin Shi Xuan (Nanyang Technological University, 2020)
Hydrophobic coatings are typically used for anti-corrosion properties such as pipelines in Oil & Gas, ships in maritime and building constructions. However, commercial hydrophobic coatings are rarely obtained from bio-epoxy resins. Thus, fabrication of water-repellent easycleaning and anti-corrosion epoxy coating can be achieved by optimizing the surface energy interaction between bio-epoxy resin and water. However, general epoxy coating are categorized as thermosets and synthesized using condensation polymerization. Epoxy coatings are usually hydrophilic in nature and fabrication of a hydrophobic epoxy film with anticorrosion properties poses a challenge. In addition, commercial epoxy resins focuses heavily on Bisphenol A (BPA). BPA have various negative impact such as endocrine disruptor which interferes with hormonal system within human. It has made such a big impact due to its good mechanical and other properties. This results in a demand to seek other epoxy producing methods without the need to use BPA The purpose of this final-year project is to synthesize a hydrophobic epoxy coating without the need for harmful organic solvents as part of the fabrication process for anti-corrosion properties. By using Glycerol diglycidyl ether which is extracted from soybean oil or various vegetable oil, a soybean-based epoxy was developed using Furfurylamine as the curing agent. Various additives such as Polydimethylsiloxane (PDMS) and Phytic Acid was explored to improve its properties. These curing agent and additives are chosen due to its bio-based compound thus its relevancy to the proposition of synthesizing a bio-epoxy coating. Characterization of the thermal, surface and chemical composition was thoroughly analysed using Thermogravimetric analysis (TGA), Differential scanning calorimetry (DSC), Fourier Transformation Infrared Spectroscopy and contact angle. The anti-corrosion properties was investigated via immersion in NaCl and potentiodynamic polarization. Comparative studies was determined to produce the optimal anti-corrosion Glycerol diglycidyl ether epoxy. Addition of PDMS showed a vast improvement in its hydrophobic properties however, showed that the hydrophobic samples does not correlate to better anti-corrosion properties. Phytic Acid while does not show an improvement in anti-corrosion properties, showed an improvement in film adhesion to the substrate. The report concludes with a discussion of its findings as well as methods to improve the sample overall properties. Overall, the results showed that the non-additives epoxy had better anti-corrosion properties.